Multi-step infrared macro-fingerprinting on leaves of phyllagathis praetermissa from different localities in peninsular Malaysia - Tan, H.P.; Ling, S.K.; Chuah, C.H. (Elsevier, 2010)
Phyllagathis praetermissa collected from Pasoh Forest Reserve (Negeri Sembilan), Ampang Forest Reserve (Selangor) and Bukit Lagong (Selangor) in Peninsular Malaysia could be differentiated based on their chemical constituents by using multi-step infrared macro-fingerprinting. This method utilized Fourier transform infrared spectroscopy, second derivative infrared spectroscopy and two-dimensional (2D) correlation infrared spectroscopy. Conventional infrared spectra showed limited differences but the second derivative infrared spectra could amplify the differences of A praetermissa collected from different localities. P. praetermissa from the three localities were grouped by using exploratory data analysis (EDA). In addition, the visual 2D-IR spectra applied with thermal perturbation enhanced the discriminant analysis of P. praetermissa more effectively. Consequently, macroscopic IR fingerprinting has been found a useful and nondestructive approach for herbal identification and quality control of traditional medicinal herbs. (C) 2009 Elsevier B.V. All rights reserved.